Evaluation of cytotoxic, apoptotic, mutagenic, and chemopreventive activities of semi-synthetic esters of gallic acid - Silva, I. C. [UNESP]; Polaquini, C. R. [UNESP]; Regasini, L. O. [UNESP]; Ferreira, H. [UNESP]; Pavan, F. R. [UNESP] (Elsevier, 2017)
Gallic acid and its derivatives are phenolic compounds widely used as food supplements in the form of capsules, liquid extracts, and ointments owing to their good antioxidant properties. Besides, these compounds are potent inhibitors of fungi, bacteria, and some viruses and possess strong antiproliferative and chemopreventive activities. However, gallic acid derivatives are also known to exert harmful effects like mutagenicity and cytotoxicity. The present study aimed to understand and explore the toxicological risks of these compounds. For this, a series of alkyl gallates with side chains varying from five to eight carbons (pentyl, hexyl, heptyl, and octyl gallates) were evaluated for their cytotoxic and pro-apoptotic potential. In addition, the genotoxic effects of alkyl gallates were measured in HepG2 cells using the single cell gel electrophoresis (SCGE)/comet assay and the cytokinesis-blocked micronucleus (CBMN) test. In both the tests, the substances did not induce any significant differences when compared to the control group. In addition, alkyl gallates exhibited a chemopreventive effect, thereby considerably reducing the mutagenicity caused by H2O2. In conclusion, our results suggest that alkyl gallates are non-genotoxic, non-mutagenic, and pro-apoptotic agents, which may serve as suitable and promising candidates for preventing chemically-induced chromosomal damage.
Keywords: Alkyl gallates; Cell death; Chemoprotective; DNA damage; Micronucleus; Toxicity